Increasing Community Nutrition Awareness through Balanced Nutrition Education Program - Sulistyani Prabu Aji; Sumarmi Sumarmi; Rida' Millati; Yoga Tri Wijayanti; Indrawati Aris Tyarini (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2024)
Public health is a vital aspect in the development of a country. One of the key factors affecting health is balanced nutrition. Despite this, awareness of the importance of nutrition is often low in many societies, especially in developing countries. To overcome this challenge, balanced nutrition education programs have become one of the effective strategies. This program aims to increase public knowledge and awareness about the importance of balanced nutrition and encourage behavior change towards a healthier diet. Program implementation methods include identification of needs, development of appropriate educational materials, program implementation involving various related parties, periodic evaluation, and program adjustments as needed. The results of this program include increased knowledge of community nutrition, changes in healthier eating behaviors, and improved overall health and well-being of the community. The success of balanced nutrition education programs shows that this approach is effective in raising people's nutrition awareness and encouraging positive behavior change. However, sustainability and innovation development challenges still need to be addressed to achieve broader and sustainable impact in the long term. With strong commitment and cross-sector cooperation, balanced nutrition education programs have the potential to significantly improve the quality of life and welfare of the community